Bleaching internal untuk merawat perubahan warna gigi insisivus sentralis kanan atas (Laporan Kasus)Internal bleaching as a treatment to color-changed of right upper centralis canine (case report) - Firsta Dianty; Endang Sukartini; Milly Armilia (DiscoverSys Inc., 2011)
Intracoronal bleeding in the tooth pulp due to trauma is one of the causes of tooth discoloration. Anterior toothdiscoloration often cause esthetic problem that affect individual perfomance. Internal bleaching is a non-vitalbleaching method performed after endodontic treatment using strong oxidator agent in pulp chamber. This casereport discusses about internal bleaching treatment with walking bleach technique on tooth 11 after endodontictreatment. Concentration of hidrogen perokxide 35% was applied for 3-7 days, this procedure was repeated untilthe tooth color was gained. The tooth color was accomplished in second visit. As conclusion is internal bleaching astreatment of tooth discoloration due to trauma can provide a good result with good endodontic treatment.